Comparable risk of recurrent ventricular tachyarrhythmias in implantable cardioverter‐defibrillator recipients treated with single beta‐blocker or combined amiodarone. Issue 3 (27th November 2020) - Schupp, Tobias; Behnes, Michael; Kim, Seung‐hyun; Müller, Julian; Weidner, Kathrin; Reiser, Linda; Huseynov, Aydin; Bollow, Armin; Borggrefe, Martin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; et al.
Abstract: This study sought to assess the prognostic impact of treatment with single beta‐blocker (BB) compared to combined therapy with BB plus amiodarone (BB‐AMIO) on recurrences of ventricular tachyarrhythmias in implantable cardioverter‐defibrillator (ICD) recipients. A large retrospective registry was used including consecutive ICD recipients with index episodes of ventricular tachyarrhythmias from 2002 to 2016. Patients treated with BB were compared to patients treated with BB‐AMIO. Kaplan‐Meier and Cox regression analyses were applied for the evaluation of the primary end‐point defined as first recurrences of ventricular tachyarrhythmias at five years. Secondary end‐points comprised first appropriate ICD therapies, first cardiac rehospitalization and all‐cause mortality at five years. Among 512 ICD recipients, 81% were treated with BB and 19% with BB‐AMIO. BB and BB‐AMIO were associated with comparable risk of first recurrences of ventricular tachyarrhythmias (46% vs. 43%; log rank P = .941; HR = 1.013; 95% CI 0.725‐1.415; P = .941) and appropriate ICD therapies (35% vs. 37%; log rank P = .389; HR = 0.852; 95% CI 0.591‐1.228; P = .390). BB was associated with decreased long‐term all‐cause mortality within an univariable analysis only (20% vs. 28%; log rank p = 0.023). In conclusion, BB and BB‐AMIO were associated with comparable risks regarding recurrences of ventricular tachyarrhythmias at five years.